An ingenious fluidic capacitor for complete suppression of thermal fluctuations in two-phase microchannel heat sinks. (January 2020) - Ghosh, Durga Prasad; Sharma, Deepak; Kumar, Anurag; Saha, Sandip Kumar; Raj, Rishi
Abstract: Rapid bubble growth within the confinement of microchannels leads to undesired flow oscillations. The flow regime cycles between single-phase, bubbly/slug, backflow, dryout, and rewetting regimes. The large difference between the heat transfer coefficient (HTC) in these regimes induces significant thermal fluctuations (≈ ± 5 ° C) and the overall HTC is low. The intensity of backflow and the time-span of dryout increases with heat flux. As a result, a gradual deterioration in HTC followed by a premature CHF is encountered. Here we introduce an ingenious pulse-dampener for complete mitigation of two-phase thermofluidic fluctuations in microchannel heat sinks. An inflatable latex bladder in the outlet manifold acts as a fluidic capacitor to accommodate the excess vapor. Such on-demand vapor removal weakens backflow to avoid extended dryout. In sharp contrast to the heat sinks without pulse-dampener, a relatively high and monotonically increasing HTC without any thermal fluctuations is observed in experiments with pulse-dampener. A maximum HTC of ≈270 kW/m 2 . K at a heat flux of ≈2 MW/m 2 was observed with a nanostructured microchannel heat sink. The monotonically increasing HTC suggests that the true potential of this pulse-dampener-based heat sink design is much larger than the maximum heat flux of ≈2 MW/m 2 tested in our work. Highlights: Fabricated an ingenious two-phase pulse-dampener using an inflatable latex bladder Pulse-dampener is incorporated at the outlet manifold of a microchannel heat sink. Pulse-dampener acts as a fluidic capacitor to facilitate on-demand vapor venting. Improved vapor removal weakens backflow to avoid extended dryout of microchannels. Quenching due to continuous high-frequency rewetting reduces thermal fluctuations. Relatively high and monotonically rising heat transfer coefficient up to 2 MW/m 2